Posicionamiento espacial de albergues eventuales en analogía a un probable sismo de gran magnitud en el casco colonial del cantón Guaranda - Velasco Saltos, Ricardo Paul (2018)
The present investigation carried out in the city of Guaranda, the visual planning, the capacity, the conditions, the equipment and the infrastructure of the existing shelters near the colonial helmet of the city of Guaranda to establish its spatial location in relation to the zones at risk of terrorism with its accessibility, thus knowing the established reality of temporary shelters with suitable conditions and located in safe areas making analogy to a probable earthquake of great magnitude that violates the living conditions of the inhabitants of the colonial town of Guaranda. An investigation of the causal type shows us that there will not be sufficient response capacity or the conditions of the existing shelters near the colonial helmet in the city of Guaranda to cover the affected population in the areas at risk in the face of a possible earthquake, which conditions of good habitat for the vulnerable. In order to develop the results of the study, the bibliography, interviews with the participation of officials convenient to the project, as well as field visits, which verify the conditions and location in Zone 2 of earthquake risks of the existing shelters, MIES shelter, are exploited. , hostel Roberto Arregui CH and La Paz, for what reason that we expose 2 temporary shelters, Old Hospital Hostel and Galo Miño Complex, with their due studies to locate them in the zone of risks before earthquakes 1 and their conditions for their certification, nevertheless , it is necessary that the present study and the proposal be socialized and validated by the authority in the field of study, so that in this way the city of Guaranda is a pioneer in the path of the culture of risk management in the country.